Preoperative cognitive profile predictive of cognitive decline after subthalamic deep brain stimulation in Parkinson's disease - Mana, Josef; Bezdicek, Ondrej; Růžička, Filip; Lasica, Andrej; Šmídová, Anna; Klempířová, Olga; Nikolai, Tomáš; Uhrová, Tereza; Růžička, Evžen; Urgošík, Dušan; Jech, Robert (European journal of neuroscience, 2024)
Cognitive decline represents a severe non-motor symptom of Parkinson's disease (PD) that can significantly reduce the benefits of subthalamic deep brain stimulation (STN DBS). Here, we aimed to describe post-surgery cognitive decline and identify pre-surgery cognitive profile associated with faster decline in STN DBS-treated PD patients. A retrospective observational study of 126 PD patients treated by STN DBS combined with oral dopaminergic therapy followed for 3.54 years on average (SD = 2.32) with repeated assessments of cognition was conducted. Pre-surgery cognitive profile was obtained via a comprehensive neuropsychological examination and data analysed using exploratory factor analysis and Bayesian generalized linear mixed models. On the whole, we observed a mild annual cognitive decline of 0.90 points from a total of 144 points in the Mattis Dementia Rating Scale (95% posterior probability interval [-1.19, -0.62]) with high inter-individual variability. However, true score changes did not reach previously reported reliable change cut-offs. Executive deficit was the only pre-surgery cognitive variable to reliably predict the rate of post-surgery cognitive decline. On the other hand, exploratory analysis of electrode localization did not yield any statistically clear results. Overall, our data and models imply mild gradual average annual post-surgery cognitive decline with high inter-individual variability in STN DBS-treated PD patients. Nonetheless, patients with worse long-term cognitive prognosis can be reliably identified via pre-surgery examination of executive functions. To further increase the utility of our results, we demonstrate how our models can help with disentangling true score changes from measurement error in future studies of post-surgery cognitive changes.
Keywords: kognice; Cognitive Dysfunction; nucleus subthalamicus; lidé; Middle Aged; Parkinson Disease; Parkinsonova nemoc; Cognition; Subthalamic Nucleus; neuropsychologické testy; Female; retrospektivní studie; Humans; Neuropsychological Tests; lidé středního věku; mužské pohlaví; Deep Brain Stimulation; ženské pohlaví; Male; Aged; Retrospective Studies; kognitivní dysfunkce; hluboká mozková stimulace; senioři